Human genetic variation recognizes functional elements in noncoding sequence - Lomelin, David; Jorgenson, Eric; Risch, Neil

(untitled) (Genome Research, 2010)
Noncoding DNA, particularly intronic DNA, harbors important functional elements that affect gene expression and RNA splicing. Yet, it is unclear which specific noncoding sites are essential for gene function and regulation. To identify functional elements in noncoding DNA, we characterized genetic variation within introns using ethnically diverse human polymorphism data from three public databases—PMT, NIEHS, and SeattleSNPs. We demonstrate that positions within introns corresponding to known functional elements involved in pre-mRNA splicing, including the branch site, splice sites, and polypyrimidine tract show reduced levels of genetic variation. Additionally, we observed regions of reduced genetic variation that are candidates for distance-dependent localization sites of functional elements, possibly intronic splicing enhancers (ISEs). Using several bioinformatics approaches, we provide additional evidence that supports our hypotheses that these regions correspond to ISEs. We conclude that studies of genetic variation can successfully discriminate and identify functional elements in noncoding regions. As more noncoding sequence data become available, the methods employed here can be utilized to identify additional functional elements in the human genome and provide possible explanations for phenotypic associations.